Enhanced Mental Health with Virtual Reality Mental Hygiene by a Veteran Suffering from PTSD - Bo Søndergaard Jensen; Niels Andersen; Jes Petersen; Lene Nyboe (Case Reports in Psychiatry)
This paper describes the application and feasibility of the use of Virtual Reality Mental Hygiene (VRMH) as a mean to reduce anxiety and stress in a Danish veteran suffering from posttraumatic stress disorder (PTSD) and enduring personality change after a catastrophic experience. The results from this case study provide preliminary evidence that VRMH can be used as a mean to reduce arousal in patients with severe PTSD.